Changes in weight, physical and psychosocial patient-reported outcomes among obese women receiving treatment for early-stage breast cancer: A nationwide clinical study. (August 2020) - Di Meglio, Antonio; Michiels, Stefan; Jones, Lee W.; El-Mouhebb, Mayssam; Ferreira, Arlindo R.; Martin, Elise; Matias, Margarida; Lohmann, Ana Elisa; Joly, Florence; Vanlemmens, Laurence; Everhard, Sibille; Martin, Anne-Laure; et al.
Abstract: Background: Evidence on how weight loss correlates to health-related quality-of-life (HRQOL) among obese breast cancer (BC) patients is limited. We aimed to evaluate associations between weight changes and HRQOL. Methods: We included 993 obese women with stage I-II-III BC from CANTO, a multicenter, prospective cohort collecting longitudinal, objectively-assessed anthropometric measures and HRQOL data (NCT01993498). Associations between weight changes (±5% between diagnosis and post-treatment [shortly after completion of surgery, adjuvant chemo- or radiation-therapy]) and patient-reported HRQOL (EORTC QLQ-C30/B23) were comprehensively evaluated. Changes in HRQOL and odds of severely impaired HRQOL were assessed using multivariable generalized estimating equations and logistic regression, respectively. Results: 14.1% women gained weight, 67.3% remained stable and 18.6% lost weight. Significant decreases in functional status and exacerbation of symptoms were observed overall post-treatment. Compared to gaining weight or remaining stable, obese women who lost weight experienced less of a decline in HRQOL, reporting better physical function (mean change [95%CI] for gain, stability and loss: −12.9 [-16.5, -9.3],  −6.9 [-8.2, -5.5] and −6.2 [-8.7, -3.7]; pinteraction[weight-change-by-time]  = 0.006), less dyspnea (+18.9 [+12.3, +25.6],  +9.2 [+6.5, +11.9] and +3.2 [-1.0, +7.3]; pinteraction  = 0.0003), and fewer breast symptoms (+22.1 [+16.8, +27.3],  +18.0 [+15.7, +20.3] and +13.4 [+9.0, +17.2]; pinteraction  = 0.044). Weight loss was also significantly associated with reduced odds of severe pain compared with weight gain (OR [95%CI] = 0.51 [0.31–0.86], p = 0.011) or stability (OR [95%CI] = 0.62 [0.41–0.95], p = 0.029). No associations between weight loss and worsening of other physical or psychosocial parameters were found. Conclusions: This large contemporary study suggests that weight loss among obese BC patients during early survivorship was associated with better patient-reported outcomes, without evidence of worsened functionality or symptomatology in any domain of HRQOL. Highlights: One-in-five women was obese at diagnosis of early breast cancer. Patient-reported quality of life significantly worsened after breast cancer treatment. Weight changes were associated to changes in quality of life post-treatment. Weight loss was not associated with worse functionality or symptomatology.